(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2011)
Thepurpose of the study is to determine the role of information technology among the sportsmanagers. Subjects included 30 sports managers or physical education teachers /head of the physical education department of public schools in Gwalior, M.P. Finaldrafted questionnaire with 30 questions was used for data collection andstandardization. The questionnaire was administered individually to eachsubject. All the subjects were instructed give frank and true opinions. Forfinding out the significance of the differences of mean among the various itemsof the questionnaire. Chi-square analysis was applied. The results indicatethat information technology is very essential part for the physical education.Every sport manager must have the adequate knowledge of information technologyas well as the implementation of information technology in the physicaleducation.